2022
DOI: 10.1111/ijpo.12975
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between weight status and academic achievement in primary school children

Abstract: Background: Evidence for longitudinal associations between childhood weight status and academic achievement remains unclear due to considerable heterogeneity in study design, measures of academic achievement and appropriate categorization of weight status.Objective: To examine longitudinal associations between childhood weight status (underweight, healthy weight, overweight/obese) and academic achievement in the transition from preschool to primary (elementary) school among Australian school children. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Although the continuous form of BMI is widely used in previous CLPM studies (42)(43)(44) , future studies will need to consider different thresholds for BMI as well as alternative body weight measures (e.g. waist circumference or waist hip ratio), which may better predict outcome variables (3) . For now, BMI is the best child weight indicator that we can obtain from the ECLS-K. Future studies may also need to consider alternative CLPM that can take into account a nested structure of data where individuals are cross-classified.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the continuous form of BMI is widely used in previous CLPM studies (42)(43)(44) , future studies will need to consider different thresholds for BMI as well as alternative body weight measures (e.g. waist circumference or waist hip ratio), which may better predict outcome variables (3) . For now, BMI is the best child weight indicator that we can obtain from the ECLS-K. Future studies may also need to consider alternative CLPM that can take into account a nested structure of data where individuals are cross-classified.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The negative association between BMI and academic achievement (AA) is well documented, particularly for girls (1)(2)(3) . This association is believed to reflect a causal effect of BMI, partly due to internalisation of the social stigma associated with body weight (4)(5)(6) or to more direct physiological mechanisms including impaired brain development (7) .…”
mentioning
confidence: 99%
“…Obesity has reached epidemic proportions globally, with childhood obesity becoming one of the most pressing issues in public health, clinical practice and research [1]. Childhood obesity is closely associated with adult obesity, morbidity and mortality [2] and also linked to important academic outcomes [3]. Previous studies have for example reported associations between childhood obesity and academic performance [4], negative teacher evaluation [5], and poor mental health [6].…”
Section: Introductionmentioning
confidence: 99%